The substance and value of Italian si - Davis, Joseph, 1958- (Studies in functional and structural linguistics ;, 2017)
This book offers an original treatment of the Italian clitic si. Sharply separating encoded grammar from inference in discourse, it proposes a unitary meaning for si, including impersonals, passives, and reflexives. Si signals third-person participancy but makes no distinctions of number, gender, or case role. The analysis advances the Columbia School framework by relying on just these straightforward oppositions, attributing variety of interpretation largely to language use rather than to grammar. The analysis places si within a network of oppositions involving all the other clitics. Data come primarily from twentieth-century and more recent published and on-line literature. The book will be of interest to functional linguists, students of reflexivity, and scholars of the Italian language.